PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) TERHADAP PERENCANAAN DAN PELAKSANAAN ANGGARAN DANA DESA DI KECAMATAN MENTAYA HULU KABUPATEN KOTAWARINGIN TIMUR - Bahrujianor Bahrujianor; Mutmainah Mutmainah; Leliana Maria Angela (Universitas Palangka Raya, 2021)
The purpose in this research is to test the influence of government internal control system to the planning and implementation of Village Fund budget in Mentaya Hulu Sub-district, East Kotawarwants Regency both partially and simultaneously. The research method used to analyse this research is quantitative with a descriptive format that aims to describe, summarize the various conditions, situations or various variables present in the village apparatus. The population in this research is the entire village and sub-district apparatus consisting of 16 villages 1 village and 1 sub district with research samples as much as 189 respondents. the control environment significantly affects the implementation of village funds budget. Risk assessment is a significant impact on the budget planning of village funds. risk assessments have significant effect on the implementation of village budget funds